HUBUNGAN BEKERJA PART-TIME DENGAN AKTIVITAS BELAJAR MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS MULAWARMAN TAHUN AKADEMIK 2019/2020 - Ellyawati, Noor; Sulfikar, Sulfikar; Destari, Dina; Rahayu, Vitria Puri (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This research seeks to determine the relationship of part-time working and learning activities of economics education students at Teacher Training and Education Faculty in Mulawarman University 2019/2020 academic year by using quantitative method. The study's population was drawn from all part-time economic education students, a total of 20 persons. Product moment correlation, validity and reliability tests, and questionnaires were utilized to obtain data from respondents. According to the findings, part time working is related to the learning activities. The product moment correlation test showed part-time working has a significance level of 0.001 less than 0.005 and a value of rcount > rtable of 0.682 > 0.444, indicating that the correlation strength is